2017
DOI: 10.1177/1469066717741747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wavelength, fluence, and dose on fragmentation pathways and photoproduct ion yield in 213 nm and 266 nm ultraviolet photodissociation experiments

Abstract: Ultraviolet photodissociation tandem mass spectrometry is a powerful tool to investigate the structure of biomolecules, due to its ability to generate rich fragmentation patterns or bond selective cleavage, as a function of used laser wavelength, laser fluence, dose (number of accumulated laser pulses), and available chromophores. Herein, we report first results obtained with a newly developed two-wavelength (266 nm and 213 nm) ultraviolet photodissociation setup coupled to a Fourier-transform ion cyclotron re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…HCD was performed on the Q Exactive instrument, whereas the LTQ FT Ultra was used for ion trap CID and UVPD at 213 nm as described previously. 54 Normalized collision energy (NCE) were tested for CID and HCD (Figure S-1) and best results (highest sn-2 selectivity) were obtained for NCE 12 for LTQ-FT Ultra and NCE 10 for Q Exactive experiments. UVPD with 213 nm laser light was performed with 40 laser pulses but the fragment ion identity does not depend on the number of laser pulses.…”
mentioning
confidence: 99%
“…HCD was performed on the Q Exactive instrument, whereas the LTQ FT Ultra was used for ion trap CID and UVPD at 213 nm as described previously. 54 Normalized collision energy (NCE) were tested for CID and HCD (Figure S-1) and best results (highest sn-2 selectivity) were obtained for NCE 12 for LTQ-FT Ultra and NCE 10 for Q Exactive experiments. UVPD with 213 nm laser light was performed with 40 laser pulses but the fragment ion identity does not depend on the number of laser pulses.…”
mentioning
confidence: 99%
“…In addition to product ions from the saccharide moieties of these compounds, diagnostic ions for FA side chains and the sphingoid base helped to extensively characterize the structure of these complex lipids. Follow-up studies showed that optimized experimental settings enable identification of DB positions [77,78], sn-isomers [77,79,80], hydroxylation sites as well as linkages [81], and FA branching/ cylclopropanation [82] sites in glycerophospholipids and sphingolipids when using 193 nm or 213 nm UVPD. All these studies showed that UVPD results in extensive metabolite and lipid fragmentation, thereby enabling annotation of structural details not accessible with CID methodologies.…”
Section: Photon-based Fragmentationmentioning
confidence: 99%
“…For the latter case mentioned above, the methods of gas‐phase photon action spectroscopy in the IR or UV regions provide unique and valuable information about their structures and relative dynamics 38–50 . However, the collection of spectra usually needs longer time and higher requirements for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, infrared multiphoton dissociation (IRMPD) induces glycosidic bond cleavages and generates B/Y‐ and C/Z‐type ions, according to the Domon–Costello nomenclature of carbohydrate fragmentation 53 . For UVPD and radical‐related dissociation methods, complementary fragment ions to those observed in CID, higher‐energy collisional dissociation (HCD) and IRMPD, relative to cross‐ring cleavages, could also be observed, allowing elucidation of the glycan moiety 49 . Thus, the combination of the two different fragmentation methods can provide richer fragmentation patterns and structural information, making isomer differentiation easier.…”
Section: Introductionmentioning
confidence: 99%